The role of climate and food availability on driving decadal abundance patterns of highly migratory pelagic predators in the Bay of Biscay - Louzao, Maite; Afán, Isabel; Santos, María; Brereton, Tom (Frontiers in Ecology and Evolution, 2015)
Within the current context of changing ecosystems, many organisms are experiencing phenological changes in the timing of migration. Here, we assessed whether the abundance patterns of two trans-equatorial migrating pelagic seabirds, the great shearwater and the sooty shearwater (Puffinus gravis and P. griseus, respectively), have changed over recent decades in the Bay of Biscay in relation to the main drivers shaping their migratory journey: climatic factors and food availability. Specifically, we studied the staging dynamic by estimating dates of arrival and departure, staging duration and abundance during a 16-year temporal window (1995-2010) based on monthly at-sea observations performed onboard a commercial ferry. Climatic effects were studied at two temporal scales: oceanic winds and global oscillations indices (North Atlantic Oscillation – NAO) that represent climate variability at short and long time scales, respectively. Based on oceanic winds, we also estimated a hypothetical cost of flying on a monthly basis considering wind speed and the angle between flight and wind direction. Our results showed that both great and sooty shearwaters were influenced by the large scale NAO index but the shape of the relationship was different, while the sooty shearwater was also influenced by food availability. Thus, each species might rely on different cues before and during their migration to adjust to optimal flying conditions and foraging grounds. Both species shape their arrival in the Bay of Biscay with periods of potential minimum flying costs, following their migration from the western to the eastern North Atlantic. We foresee that the quantification of flying costs can integrate different processes at the level of migration and provide a wider understanding of the migratory dynamic of pelagic predators within current changing ecosystems.